ChemInform Abstract: Electrophilic Addition of Allylic Carbocations to 2‐Cyclopropylidene‐2‐arylethanols: A Strategy to 3‐Oxabicyclo[3.2.0]heptanes. Issue 15 (15th April 2014) - Meng, Bo; Huang, Xian; Wu, Luling
Abstract The construction of 3‐oxabicyclo[3.2.0]heptanes is developed using the electrophilic addition of carbocations generated from functionalized allylic alcohols to cyclopropylidene substituted ethanols (I).